Great Expectations: An Exploration of Confidence and Knowledge in Commencing Higher Education Students - Kelly, Kate; Lock, Edward (Journal of University Teaching and Learning Practice, 2025)
Higher education providers are facing increasing pressure to support students along their education-employment pathway. One of the challenges in supporting students is understanding the expectations that they bring with them when commencing higher education. To effectively support students higher education providers, need to empower students and understand their knowledge gaps to provide a tailored approach to support. Expectations can be driven both by thoughts and feelings, and the relationship between these can have profound implications. Drawing on psychological theories (e.g. the Dunning Kruger Effect and imposter syndrome) alongside educational theory (e.g. transitional pedagogy), the present study adopts a survey-based approach to understanding the relationship between confidence and knowledge of career outcomes, and the student factors that influence them. Findings show that most students were entering university with high levels of confidence that their course would lead towards their career goal. Interestingly, low levels of confidence, where present, were not associated with demographic factors (e.g. first-in-family), but instead with degree type and knowledge of career outcomes. More than 40% of participants had high confidence regarding career outcomes despite displaying limited knowledge about such outcomes. These findings present universities with a challenging task and suggest that promoting confidence and knowledge regarding career outcomes amongst students should start by considering the type of degree they enrolled into.